Procedural outcome & risk prediction in young patients undergoing transvenous lead extraction—a GALLERY subgroup analysis - Rexha, Enida; Chung, Da-Un; Burger, Heiko; Ghaffari, Naser; Madej, Tomas; Ziaukas, Virgilijus; Hassan, Kambiz; Reichenspurner, Hermann; Gessler, Nele; Willems, Stephan; Butter, Christian; Pecha, Simon; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background The prevalence of young patients with cardiac implantable electronic devices (CIED) is steadily increasing, accompanied by a rise in the occurrence of complications related to CIEDs. Consequently, transvenous lead extraction (TLE) has become a crucial treatment approach for such individuals. Objective The purpose of this study was to examine the characteristics and procedural outcomes of young patients who undergo TLE, with a specific focus on identifying independent risk factors associated with adverse events. Methods All patients in the GALLERY (GermAn Laser Lead Extraction RegistrY) were categorized into two groups based on their age at the time of enrollment: 45 years or younger, and over 45 years. A subgroup analysis was conducted specifically for the younger population. In this analysis, predictor variables for all-cause mortality, procedural complications, and procedural failure were evaluated using multivariable analyses. Results We identified 160 patients aged 45 years or younger with a mean age of 35.3 ± 7.6 years and 42.5% (n = 68) female patients. Leading extraction indication was lead dysfunction in 51.3% of cases, followed by local infections in 20.6% and systemic infections in 16.9%. The most common device to be extracted were implantable cardioverter-defibrillators (ICD) with 52.5%. Mean number of leads per patient was 2.2 ± 1.0. Median age of the oldest indwelling lead was 91.5 [54.75–137.5] months. Overall complication rate was 3.8% with 1.9% minor and 1.9% major complications. Complete procedural success was achieved in 90.6% of cases. Clinical procedural success rate was 98.1%. Procedure-related mortality was 0.0%. The all-cause in-hospital mortality rate was 2.5%, with septic shock identified as the primary cause of mortality. Multivariable analysis revealed CKD (OR: 19.0; 95% CI: 1.84–194.9; p = 0.018) and systemic infection (OR: 12.7; 95% CI: 1.14–142.8; p = 0.039) as independent predictor for all-cause mortality. Lead age ≥ 10 years (OR: 14.58, 95% CI: 1.36–156.2; p = 0.027) was identified as sole independent risk factor for procedural complication. Conclusion TLE in young patients is safe and effective with a procedure-related mortality rate of 0.0%. CKD and systemic infection are predictors for all-cause mortality, whereas lead age ≥ 10 years was identified as independent risk factor for procedural complications in young patients undergoing TLE.